2018
DOI: 10.1159/000488231
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose-Induced Podocyte Injury Involves Activation of Mammalian Target of Rapamycin (mTOR)-Induced Endoplasmic Reticulum (ER) Stress

Abstract: Background/Aims: The mechanisms by which high glucose (HG) results in podocyte damage remains unclear. We investigated the potential role of endoplasmic reticulum (ER) stress and mTOR signaling in HG injured podocyte. Methods: In cultured mouse podocytes, cellular apoptosis was assessed using FITC-Annexin V and propidium iodide staining followed by flow cytometry analysis. Apoptosis-related proteins as well as the ER stress and the mTOR signals were evaluated using immunoblot assay. Results: Compared to normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…113,[135][136][137][138][139][140][141] It is well established that ER stress pathways are activated in fibrotic renal disease, including in diabetic nephropathy and in ischemia, and that chemical chaperones such as 4-phenylbutyrate and tauroursodeoxycholic acid have been shown to reduce ER stress and result in fibrosis in animal models of renal disease. [142][143][144][145][146][147][148][149] It is unclear how TSP1 and other TSP family members might be participating in the UPR and other branches of the ER stress response and whether intracellular TSP1 functions are involved in fibrogenic processes. Studies on mutant COMP (TSP5) in models of pseudoachondroplasia showed a more severe phenotype in animals in which the mutant protein was expressed than in knockout mice.…”
Section: Intracellular Tsp1 As An Er Stress Regulator Of Ecmmentioning
confidence: 99%
“…113,[135][136][137][138][139][140][141] It is well established that ER stress pathways are activated in fibrotic renal disease, including in diabetic nephropathy and in ischemia, and that chemical chaperones such as 4-phenylbutyrate and tauroursodeoxycholic acid have been shown to reduce ER stress and result in fibrosis in animal models of renal disease. [142][143][144][145][146][147][148][149] It is unclear how TSP1 and other TSP family members might be participating in the UPR and other branches of the ER stress response and whether intracellular TSP1 functions are involved in fibrogenic processes. Studies on mutant COMP (TSP5) in models of pseudoachondroplasia showed a more severe phenotype in animals in which the mutant protein was expressed than in knockout mice.…”
Section: Intracellular Tsp1 As An Er Stress Regulator Of Ecmmentioning
confidence: 99%
“…Inhibition of the PI3K-AKT-mTOR pathway can activate autophagy [33]. However, inhibition of mTOR by pharmacological agents, such as rapamycin, can prevent cellular apopotosis induced by HG-treatment [34] and promote AKT phosphorylation by blocking the phosphorylation of insulin receptor substrate 1 and p70 ribosomal S6 kinase [32,35], which are part of a negative feedback mechanism of PI3K-AKT signal transduction [36]. Our results demonstrate that LN inhibits mTOR, but increases the phosphorylation of AKT, suggesting that LN inhibited mTOR independent of AKT activation.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…High blood glucose level causes the damage of glomerular and podocyte [61]. In this paper, the positive drug, Irbesartan, was not a hypoglycemic drug, but it showed the hypoglycemic effect which deserves further study.…”
Section: Discussionmentioning
confidence: 91%